Дослідження у Києві по вул. Лук’янівська, 19 - Козловський, А.О.; Ієвлев, М.М.; Крижановський, В.О. (Археологічні дослідження в Україні, 2010)
Results of the excavations at Shchekavytsya Mount in the historic part of Ancient Kyiv are presented. Husbandry structure and pit have been partly uncovered. Apparently they were a part of the Ancient Rus dwelling and husbandry complex the main part of which was ruined by construction activities. The objects are dated from the beginning of the 11th c. to the 12th c.